Performance of intensive vannamei (Litopenaeus vannamei) culture at low salinity - Annisa Bias Cahyanurani; Mochammad Heri Edy (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
Intensive aquaculture systems that are not managed properly often cause problems that disrupt the balance of the environment so that shrimp are susceptible to disease. One of the aquaculture innovations that have been developed to minimize disease impact is shrimp farming with low salinity. This study aims to determine the performance of intensive Litopenaeus vannamei shrimp culture with low salinity. This study used quantitative descriptive analysis with a purposive sampling technique in three ponds for three maintenance cycles. The result of the study on three cycles of vannamei shrimp culture with low salinity overall found that productivity ranged from 2.35 to 3.69 kg/m2. ADG values in aquaculture ponds ranged from 0.26 0.36 g/day. The survival rate ranged from 61% to 98%, and the feed conversion ratio ranged from 1.01 to 1.62. The survival rate tends to increase, and FCR value tends to decrease in 3 cycles of cultivation. Water quality including temperature, dissolved oxygen, pH, phosphate, ammonia, and TOM indicate the optimal range based on water quality standards for intensive vannamei shrimp culture (SNI 01-7246-2006). At the same time, nitrite and alkalinity exceed the SNI standard but this nitrite and alkalinity level could still be tolerated by vannamei shrimp during the rearing period. Overall, water quality during the rearing period can still support the growth of vannamei shrimp. The above result showed that vannamei shrimp culture at low salinity (6-8 mg L-1) has the potential to be developed.Keywords:Intensive culture Litopenaeus vannamei Low salinityProductivity